Identifikasi Pemilihan Konsumen Kartu Kredit di Indonesia - Ilham Prisgunanto (Fakultas Ilmu Komunikasi Universitas Pancasila, 2017)
Ecommerce has been coming to people live so banking would to change any transactions from money to credit card. All people know that socialization using credit card to real electronic society base on how did banking identificate their consumers. This study would to talked about would bank makes identification their consumers and applying their strategies and tactis promotions for marketing credit card product. This papers applied any teoretical studies likes customer behaviours, strategic management, STP analysis. This research used qualitative analysis data and descriptive models. Any interview had been completely for five banking industry which give credit card services likes Mandiri bank, HSBC, BCA bank, Citibank dan BNI. Finding of this research talked that bank leaders (Citi Bank) was more best maked good preparation for identification their consumers and applying their strategies and tactis promotions for marketing credit card products than follower bank (Bank HSBC, BCA, Mandiri dan BNI). Beside it the followers bank just focus to intervention market for local consumers and give new any concept credit card for family lives. All people know that any socialization and promotion for credit card using mainstream media likes television, radio and press, fewer with the digital media. This is any reason why banking can’t succesfull to make electronic society in cyber and digital era.